Identification of rare variants in Alzheimer’s disease - Lord, Jenny; Lu, Alexander J.; Cruchaga, Carlos (Frontiers in Genetics, 2014)
Much progress has been made in recent years in identifying genes involved in the risk of 16 developing Alzheimer’s disease (AD), the most common form of dementia. Yet despite the identification of over disease associated loci, mainly through genome wide association studies, a large proportion of the genetic component of the disorder remains unexplained. Recent evidence from the AD field, as with other complex diseases, suggests a large proportion of this “missing heritability” may be due to rare variants of moderate to large effect size, but the methodologies to detect such variants are still in their infancy. The latest studies in the field have been focused on the identification of coding variation associated with AD risk, through whole-exome or whole-genome sequencing. Such variants are expected to have larger effect sizes than GWAS loci, and are easier to functionally characterize, and develop cellular and animal models. This review explores the issues involved in detecting rare variant associations in the context of Alzheimer’s disease, highlighting some successful approaches utilized to date.